Turks in Early Arabic Sources: A Modus Analysis of Ahmad Ibn Fadlan’s Manuscript Describing His Journey to the Volga - Ahmed Mohammed Nasser Al-Rahbi; Viktoriya N. Zarytovskaya; Renata S. Faizova (Oriental Studies, 2021)
Introduction. The article examines the subjectivity in the representation of Turkic clans in ibn Fadlan’s famous memoirs devoted to the Arab mission trip undertaken from Baghdad to the Volga Bulgaria in early 10th c. Informed by the latest linguistic theories, the authors aim to analyze how the modus of his text, i.e. the meaning of the entire historical document, is influenced by the memoirist’s personality as a bearer of certain cultural characteristics and of specific religious beliefs, as well as by historical and everyday circumstances at the time the travelogue was written. Data and methods. Both the reconstructed Arabic original and available Russian translations and commentaries were used in a comparative mode. In addition, the authors considered the recent works of Arab scholars discussing the issue of discourse types of ibn Fadlan’s heritage in the context of the medieval Arab history and thinking. The article focuses on the prevailing themes and motifs in the text of the Arab traveler, when describing the social structures, traditions, and rituals of the Turkic ethnic groups he encountered (chiefly Oguzes), to identify the moduses (of condemnation, fear, surprise, admiration, etc.) through which these were realized, as well as the linguistic means of their expression that disturbed the neutral style of the story. The results of the analysis allow to draw a conclusion that the modus of the work was largely shaped by the medieval way of thinking and the world picture characteristic of the Arab-Muslim traveler, as well as by the official status of ibn Fadlan’s work at the court of the Abbasid Caliphate in its heyday. Also, the authors point out that there is a passage in the text that may be fictional, its morphology being largely of a fabulous character. Notably, attention should be drawn to ibn Fadlan’s attempts to find some possible commonalities between the civilizations, especially in the heavenly realm, and to promote an understanding between the peoples, even if neither cultural nor trade interaction between them existed at the time.